Impact of Mid-Life Symptoms of Alcoholism on the Health and Wellbeing of Aging Parents of Adults with Disabilities. Issue 1 (2nd January 2016) - Ghosh, Subharati; Ha, Jung-Hwa; Pai, Manacy; Essenfeld, Harper; Park, Sang Min
ABSTRACT: The study examined the effect of adult children's disability on parents' physical health in later life and the extent to which parents' symptoms of alcoholism in mid-life moderates the link between children's disability and later life parental health. Analyses are based on data from the Wisconsin Longitudinal Study. The analytic sample included parents of children with developmental disabilities ( n  = 145) or mental health problems ( n  = 200) and 2, 432 parents of unaffected children. The results showed that the negative health consequences in later life of having a child with a developmental disability were greater for those who showed more symptoms of alcoholism in mid-life. However, symptoms of alcoholism in mid-life did not significantly moderate the impact of an adult child's mental health problems on parents' later life physical health. The findings suggest a potential area where gerontological social workers could intervene, given the negative impact of symptoms of alcoholism on the health of aging parents of children with a disability who may be significantly more susceptible to the negative health impacts of alcohol compared to their younger counterparts.